Determination Of Marketing Performance Of SMEs In Bandar Lampung City - Tri Lestira Putri Warganegara; Nurdiawansyah Nurdiawansyah; Luke Suciyati Amna (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this research is to look at the implications of entrepreneurial orientation, product innovation, digital marketing, and competitive advantage on the marketing performance of culinary micro, small, and medium companies (SMEs) in Bandar Lampung. The sample for the study includes 53 culinary SMEs entrepreneurs from Bandar Lampung City. This research employs quantitative research methods and data analysis using IBM SPSS Statistics 26. According to the preliminary findings, digital marketing and competitive advantage have a positive impact on marketing performance, however entrepreneurial consideration and product innovation have no significant impact. Furthermore, concurrent testing show that entrepreneurial orientation, product innovation, and competitive advantage all have an impact on marketing performance. These findings will assist culinary SMEs in Bandar Lampung to strengthen their marketing performance. Increasing a competitive advantage can be an effective approach for increasing company competitiveness, although the value of entrepreneurial orientation and product innovation should also be taken into account in order to get better marketing results. In an era of rising business competitiveness, this inquiry can serve as a platform for managerial choices on how to advance and growth of the SMEs culinary industry in Bandar Lampung.